Comparative analysis of morphologival parameters in isolated and fused L5 spondylolysis patients on the basis of CT features - Rui Ma; Xiaoxia Huang; Luyao Li; Ye Kai; Jun Liu; Gao Leilei; Xiangning Sun; Yong Teng (BMC Musculoskeletal Disorders)
Abstract Background and objective The classification of lumbar spondylolysis varies, and there is currently no clear consensus on a standardized system. This study examines the morphological characteristics and parameter differences of the L5 vertebra in patients with isolated versus fused spondylolysis using CT measurements. It also proposes a preliminary classification system based on the separation distance at the fracture site and explores its clinical significance. Methods A total of 117 young male patients with L5 spondylolysis related to high-intensity physical activity were enrolled. Patients with a pars interarticularis separation distance ≥ 2 mm were classified into the isolated group (Group A, 66 patients), while those with a separation distance < 1 mm were classified into the fused group (Group B, 51 patients).Additionally, 117 patients without spondylolysis but experiencing lower back pain were included as the control group (group C). Multislice spiral computed tomography (MSCT) was used to measure the morphological parameters of the L5 vertebra in all three groups, including the sagittal pedicle height (SPH), transverse pedicle width (TPW), transverse pedicle vertical length (TPVL), pedicle screw trajectory length (PSTL), pedicle angle of attack (PAA), frontal vertebral body height (FVH), posterior vertebral body height (PVH), sagittal midline intervertebral space height (SMISH), horizontal vertebral body angle (HVA), and vertical vertebral body angle (VVA). Differences in the morphological imaging parameters of the L5 vertebrae and pedicles among the three groups were compared. Results There were no significant differences in age, height, weight, body mass index (BMI), or Pfirrmann grade among the three groups. No significant differences were observed in any of the pedicle parameters between the left and right sides within the groups. Group A showed significantly greater TPVL and PSTL values compared to Group B, while TPW and PAA were significantly lower. No significant difference in SPH was observed between Group A and Group B. When compared to Group C, Group A exhibited significant differences in SPH, TPW, TPVL, and PSTL, but not in PAA. Group B, compared to Group C, demonstrated significant differences in SPH and PAA, but no significant differences were observed in TPW, TPVL, or PSTL. Significant differences were also found in FVH, HVA, and VVA between Group A and Group B, with Group A showing a smaller PVH. No significant difference in SMISH was observed between the two groups. Compared to Group C, Group A showed significant differences in PVH, HVA, and VVA, but no significant differences were found in FVH or SMISH. In Group B, significant differences were noted in FVH and HVA compared to Group C, but no differences were observed in PVH, SMISH, or VVA. Conclusion Differences in the sagittal morphological parameters of the pedicles and vertebral bodies can be observed between the two types of spondylolysis patients. In the isolated spondylolysis pattern, the pedicles exhibit a "thin, long, and contracted" morphology, while the vertebral bodies present a "stuffed bun" shape, both anteriorly, posteriorly, and superiorly. In contrast, the fused type is characterized by "short, thick, and expanded" pedicles, with the vertebral bodies showing a "less pronounced stuffed bun" shape in the anterior–posterior direction. These morphological differences indicate that spondylolysis separation may involve adaptive stress-induced bone remodeling. Surgeons must pay special attention when choosing surgical techniques, as isolated spondylolysis may present a tendency toward slippage. Caution is advised in performing isolated pars repair surgeries, especially during the placement of pedicle screws, where special attention must be given to the length and direction of the screws to avoid additional damage.